Blunted Expansion of Regulatory T Lymphocytes Is Associated With Increased Bacterial Translocation in Patients With Major Depressive Disorder - Alvarez-Mon, Miguel Angel; Gomez-Lahoz, Ana Maria; Orozco, Arantxa; Lahera, Guillermo; Sosa-Reina, M. Dolores; Diaz, David; Albillos, Agustin; Quintero, Javier; Molero, Patricio; Monserrat, Jorge; Alvarez-Mon, Melchor (Frontiers in Psychiatry, 2021)
Background: Major Depressive Disorder (MDD) is associated with both proinflammatory and adaptive immune response abnormalities. Regulatory T lymphocytes (Tregs), a subtype of CD4+ T cells, are relevant for maintaining immune-inflammatory system homeostasis and control of inflammation such as the kind potentially induced by the interactions between the intestinal microbiome and gut mucosa. We investigated the Treg population and its distribution along their stages of differentiation/activation, as well as its function in MDD patients without concomitant diseases. We also studied the potential association between Treg alterations, intestinal barrier damage and bacterial translocation. Methods: 30 MDD patients and 20 healthy controls were studied. The levels of circulating CD25FoxP3+ Tregs and their distribution on the naïve (TN), effector (TE), central (TCM) and effector memory(TEM) differentiation/activation stages were analyzed using polychromatic ﬂow cytometry. Chemokine receptors (CCR) 2, 5 and 6, and the intracytoplasmic IL-10 expression by the Tregs were also analyzed. The serum IL-10 was measured using Luminex. The serum levels of zonulin and the intestinal fatty acid-binding protein (I-FABP), both markers of gut barrier function, and the LPS-binding protein (LBP), a marker of bacterial translocation, were measured using an enzyme-linked immunosorbent assay. Results: MDD patients had increased number of circulating Tregs cells with enhanced number of Tregs at the TN, TE, TCM and TEM stages. The percentage of Tregs cells at TN stage was significantly higher in MDD patients. The percentage of Tregs that expressed CCR2 and CCR6 was increased as well as those expressing IL-10. MDD patients had signiﬁcantly increased levels of circulating I-FABP and LBP. MDD patients with high LBP levels had a signiﬁcant reduction in the number of circulating Tregs compared to normal-LBP MDD patients. Conclusions: MDD patients showed an expansion of circulating Tregs and their CD25highFoxP3+ and CD25lowFoxP3+ subsets throughout the different stages of CD4+ T lymphocyte differentiation/activation. Tregs also showed an increased frequency of cells expressing CCR6 and CCR2. IL-10 Treg production was also enhanced in MDD patients that concurrently had increased serum IL-10 levels. However, this Treg expansion was blunted in MDD patients with gut barrier damage and increased bacterial translocation.